2009
DOI: 10.1158/1541-7786.mcr-09-0207
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-3 Is Uniquely Upregulated in Malignant Gliomas and Promotes Tumor Cell Motility and Invasion

Abstract: Malignant gliomas are highly invasive tumors with an almost invariably rapid and lethal outcome. Surgery and chemoradiotherapy fail to remove resistant tumor cells that disperse within normal tissue, which are a major cause for disease progression and therapy failure. Infiltration of the neural parenchyma is a distinctive property of malignant gliomas compared to other solid tumors. Thus, glioma cells are thought to produce unique molecular changes that remodel the neural extracellular matrix and form a microe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(166 citation statements)
references
References 59 publications
1
164
1
Order By: Relevance
“…Fibulin-3 has been found to be downregulated in several types of solid tumors (14) but surprisingly, is the most upregulated member of the fibulin family in malignant gliomas (15). Fibulin-3 is also upregulated in aggressive pancreatic adenocarcinoma, resulting in enhanced in vivo orthotopic and metastatic tumor growth (16).…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-3 has been found to be downregulated in several types of solid tumors (14) but surprisingly, is the most upregulated member of the fibulin family in malignant gliomas (15). Fibulin-3 is also upregulated in aggressive pancreatic adenocarcinoma, resulting in enhanced in vivo orthotopic and metastatic tumor growth (16).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 and MMP-2 are important ECM-degrading enzymes that are reported to be involved in cancer cell invasion and metastasis (20). On the basis of these observations and the foregoing data, we examined the effect of shikonin on the expression of both MMP-2 and MMP-9 in MDA-MB-231 cells; we also investigated PMA-induced MMP-9 expression in MCF-7 cells.…”
Section: Shikonin Inhibits Mmp-9 Expression and Proteolytic Activitymentioning
confidence: 99%
“…CADPE inhibits MMP-9 expression and activity MMP-9 and MMP-2 are important ECM-degrading enzymes. It has been reported that both enzymes were involved in cancer cell invasion and metastasis (14,29). The fact that CADPE inhibited cancer cell invasion prompted us to examine the effect of CADPE on MMPs activity using gelatin zymography.…”
Section: Effects Of Cadpe On the Viability And Invasion Of Gastric Camentioning
confidence: 99%